2020
DOI: 10.3390/su12104032
|View full text |Cite
|
Sign up to set email alerts
|

How Vulnerable Are Urban Regeneration Sites to Climate Change in Busan, South Korea?

Abstract: Research on the risks of climate change to urban regeneration projects has been insufficient to date. Therefore, this study aims to compare and analyze the degree of risk of climate change impact on areas with and without urban regeneration projects (for Eup, Myeon, and Dong regional units) in Busan, South Korea. In this study, (1) climate change risk indicators were extracted based on the concept of risk (hazard, vulnerability, and exposure), (2) a spatial analysis was performed using a graphic information sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Planners should consider upgrading the thermal efficiency of buildings to reduce both the cost of energy use in residential and commercial sectors and GHG emissions from the construction sector [34]. While residential energy use shows significant variability between temperate and cold climates [35], its correlation with urban compactness is not as strong as with energy use in the road transport sector [17,25,36,37]. Therefore, this study focused its analysis on GHG emissions from the road transport sector.…”
Section: Study Location and Emissions Datamentioning
confidence: 99%
See 3 more Smart Citations
“…Planners should consider upgrading the thermal efficiency of buildings to reduce both the cost of energy use in residential and commercial sectors and GHG emissions from the construction sector [34]. While residential energy use shows significant variability between temperate and cold climates [35], its correlation with urban compactness is not as strong as with energy use in the road transport sector [17,25,36,37]. Therefore, this study focused its analysis on GHG emissions from the road transport sector.…”
Section: Study Location and Emissions Datamentioning
confidence: 99%
“…These studies have suggested that factors including city size, policy measures such as fuel taxes, and advanced road transport infrastructure might be more effective in reducing energy use and GHG emissions. Furthermore, several studies have indicated that at the same level of compactness, polycentric cities emit less GHGs than monocentric ones [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…By employing the AHP analysis and experts' brainstorming, Kim [30] found industrial/economic and population/social aspects were highlighted more often than other elements within existing urban regeneration projects. Kang et al [31] analyzed risk indicators to investigate the degree of risk to climate change in urban regeneration project areas in Busan, Korea and discovered that those sites were more vulnerable to climate change, compared to other aging city centers. Additionally, other studies have evaluated the success and effectiveness of urban regeneration projects by conducting in-depth interviews and employing various performance assessment indicators.…”
Section: Plan Evaluationsmentioning
confidence: 99%